2011
DOI: 10.1166/jbn.2011.1199
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Interaction of Gold–Curcumin Nanoparticles with Human Peripheral Blood Lymphocytes

Abstract: The use of nano-particles in several areas necessitates the understanding of their interaction with cells, tissues and experimental animals. In the present study, the effect of a curcumin conjugated gold nano-particle on peripheral blood lymphocytes was investigated. The treated lymphocytes revealed features typical of apoptosis which include chromatin condensation, and membrane blebbing and occurrence of apoptotic bodies. The observations indicate that these nanoparticle conjugates may find use as drugs in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…A recent study suggests that PLGA, CD, cellulose, nano-gel, and dendrimer based curcumin formulations did not show any erythrocytes damage or occurrence of thrombus [50]. Similar observations were made with intravenous PLGA nanosuspensions, curcumin conjugated nanoparticles [149153], gold- curcumin nanoparticles, and a layer-by-layer self-assembly curcumin formulation [115, 135, 136, 154]. Rejinold et al [155] demonstrated the biocompatibility nature of a thermosensitive curcumin formulation by hemolysis assay.…”
Section: Curcumin Nanoformulationssupporting
confidence: 60%
“…A recent study suggests that PLGA, CD, cellulose, nano-gel, and dendrimer based curcumin formulations did not show any erythrocytes damage or occurrence of thrombus [50]. Similar observations were made with intravenous PLGA nanosuspensions, curcumin conjugated nanoparticles [149153], gold- curcumin nanoparticles, and a layer-by-layer self-assembly curcumin formulation [115, 135, 136, 154]. Rejinold et al [155] demonstrated the biocompatibility nature of a thermosensitive curcumin formulation by hemolysis assay.…”
Section: Curcumin Nanoformulationssupporting
confidence: 60%
“…Encapsulation in polymeric nanoparticles, which are aggregates of cross-linked and random copolymers, has shown promise as an effective method of delivering curcumin. [20][21][22][23][24] Recently, the use of serum albumin as a carrier for curcumin has been reported, [25][26][27][28][29][30] implying that this protein has the ability to stabilize curcumin. Wang et al have shown that degradation of curcumin in buffer solution is suppressed in the presence of serum.…”
Section: Introductionmentioning
confidence: 99%
“…The average size of the particles was nearly 58 nm with a zeta potential of -23 mv. The particles were quite stable for nearly 6 mo at room temperature and no toxicity was reported in the in vitro studies so far [79] .…”
Section: Transdermal Drug Delivery System (Tdds)mentioning
confidence: 84%